Business Model Building and Its Performance in Micro and Small Apparel Industry in Bandung City, Indonesia - Ratnaningtyas, Sudrajati; Dhewanto, Wawan; Rudito, Bambang; Agus Prasetio, Eko; Gina Karunia Kusumah, Gina (International Journal of Engineering and Technology, 2018)
This study aims to determine whether or not the impact of business size on business model building and business performance perceived owner. This research used a quantitative-qualitative approach with Survey Method. The study was conducted in Apparel industry in Bandung City in 2017. The business model used to evaluate is Business Model Canvas (BMC). Chi-Square and Mann-Whitney U tests were used to test the differences between micro business and small business on each of BMC building blocks. The results showed that BMC building blocks between Micro Business and Small Buisness differed on two blocks, ie Channels and Revenue Streams, while the other seven blocks were not different significantly. It can be interpreted that the business model on Micro Businesses is generally slightly different with Small Businesses, or in other words the business strategy is relatively the same. However, the Business Model applied to Small Business with excellence in marketing channels and revenue streams compared to Micro Business, has resulted in a higher level of owner satisfaction on the performance of its business.Â Â